2019
DOI: 10.21037/atm.2019.08.58
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of os acromiale using polyester sutures: a novel surgical treatment

Abstract: Background: Patients with unstable os acromiale often complain of shoulder pain. Numerous surgical treatment options have been introduced with inconsistent clinical results. In this study, a novel surgical treatment using polyester sutures to fix unstable os acromiale was introduced, and clinical results were reported.Methods: We retrospectively studied 10 shoulders that were diagnosed with os acromiale from January 2014 to January 2016. All 10 cases were of the meso-acromion type. Except for the first case in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…It is less time consuming and it allows improved bone contact with possible increased compression across the nonunion [ 12 ]. All suture circulage technique was reported by Guo et al [ 1 ] with reported bony fusion for all cases. Our technique has the advantage of a fully arthroscopic procedure with no need for open intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is less time consuming and it allows improved bone contact with possible increased compression across the nonunion [ 12 ]. All suture circulage technique was reported by Guo et al [ 1 ] with reported bony fusion for all cases. Our technique has the advantage of a fully arthroscopic procedure with no need for open intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Os acromiale is a developmental condition which results from failure of fusion of the secondary ossification centre. Four different ossification centres have been identified; failure of fusion of any of them results in mobile Os acromiale [ 1 ]. Its prevalence is estimated between 1 and 15% based on different studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process of bone formation is usually completed by around 25 years of age [1,5,[7][8][9][10]. Nevertheless, the reported incidence of deficient osseous fusion, leading to a disunited fragment ranged from 1 to 30% [2,4,5,8,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of unfused cases, an os acromiale is asymptomatic and incidentally detected on shoulder radiographs [ 6 – 8 , 11 , 13 ]. Alternately, painful conditions including tenderness on palpation, complaints during overhead activities, pain due to sleeping on the affected shoulder, positive signs of impingement and weakness of the rotator cuff muscles [ 6 , 7 , 10 – 12 ] frequently occur after trauma or may have atraumatic origins [ 4 , 6 – 8 ]. Symptomatic patients should initially receive conservative management involving physiotherapy, analgesia and supplementary corticoid injections for at least 6 months [ 2 , 6 9 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%